DETERMINAN MINAT MAHASISWA MENJADI AKUNTAN PUBLIK - Tantri, Octaviany; Wirajaya, I Gde Ary (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025DO - 10.24843/EEB.2025.v14.i05.p06, 2025)
The quantity of financial practitioners, especially public accountants in Indonesia, shows a tendency to decrease every year. However, there is an escalation of business entities that have been registered on the IDX. This research is intended to provide factual evidence on how much involvement in each MBKM Mandiri internship program, perceptions of labor market conditions, financial rewards contribute to students' interest in choosing a career as a public accountant. A group of individuals who will be used as a sample is determined through the saturated sampling method. This means that the entire population will be the research sample. The population consists of students from the Accounting Undergraduate Study Program who are enrolled in five universities that have good rankings from uniRank. The total sample obtained was 50 respondents. From the results of data collection, it will then be processed through multiple linear regression analysis. The findings of this research show that there are several determinants that can contribute to increasing students' interest in becoming public accountants while providing validation of the Theory of Planned Behavior (TPB).